1998
DOI: 10.1093/genetics/148.3.963
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast HSM3 Gene Acts in One of the Mismatch Repair Pathways

Abstract: Mutants with enhanced spontaneous mutability (hsm) to canavanine resistance were induced by N-methyl-N-nitrosourea in Saccharomyces cerevisiae. One bearing the hsm3-1 mutation was used for this study. This mutation does not increase sensitivity to the lethal action of different mutagens. The hsm3-1 mutation produces a mutator phenotype, enhancing the rates of spontaneous mutation to canavanine resistance and reversions of lys1-1 and his1-7. This mutation increases the rate of intragenic mitotic recombination a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Earlier in our laboratory, extensive research was carried out on the genetic properties of hsm3∆ mutation [25][26][27][28][29][30][31]. We have shown that proteins Mms2, Xrs2, Srs2, Mph1, Mms4, involved in the error-free branch of the PRR, have a crucial function in hsm3-dependent UV mutagenesis [38,43].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier in our laboratory, extensive research was carried out on the genetic properties of hsm3∆ mutation [25][26][27][28][29][30][31]. We have shown that proteins Mms2, Xrs2, Srs2, Mph1, Mms4, involved in the error-free branch of the PRR, have a crucial function in hsm3-dependent UV mutagenesis [38,43].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we have shown that mismatch repair plays a role in hsm3 -dependent mutagenesis [ 30 ]. The mutation frequency in hsm3Δ pms1Δ double mutant was significantly higher than in both single mutants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations